If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 5 = 2x + -19 Reorder the terms: 5 + 4x = 2x + -19 Reorder the terms: 5 + 4x = -19 + 2x Solving 5 + 4x = -19 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 5 + 4x + -2x = -19 + 2x + -2x Combine like terms: 4x + -2x = 2x 5 + 2x = -19 + 2x + -2x Combine like terms: 2x + -2x = 0 5 + 2x = -19 + 0 5 + 2x = -19 Add '-5' to each side of the equation. 5 + -5 + 2x = -19 + -5 Combine like terms: 5 + -5 = 0 0 + 2x = -19 + -5 2x = -19 + -5 Combine like terms: -19 + -5 = -24 2x = -24 Divide each side by '2'. x = -12 Simplifying x = -12
| x^2+x+3=10 | | (5-2i)+(3+9i)= | | 3(x+7)=40 | | (-2+4i)-(3+9i)= | | 7x-1=10x-13 | | x-72= | | 8*x=4 | | 42=3(2t-3) | | 15m-6m=9 | | 42=3(2t-3h) | | 4+-5=7 | | 4d=16 | | 6x-9=6(x+5) | | 15+q+y=-10 | | 2x=190 | | x^2-10x-25+2x^2+x-2x-1=13x+26 | | 12x-14=1.15 | | -4+y=8 | | -6b+9+4b=3b+14 | | 3x+2=5x+74 | | -2.4r=1.2 | | y+y=2 | | 9-2b=3b+14 | | 4p+25=40 | | x+(x+8)+(x-3)=64 | | 10+r=-4 | | 7-4(-2+x)=31 | | p=s^2+11s-28 | | -5(x-5)=-4x | | 6x+4x=-3 | | 24-10x=-4x | | 14x+3=157-4x+10 |